PEMBENTUKAN NILAI MORAL SISWA DENGAN MEMANFAATKAN KEARIFAN LOKAL PADA TEMA 7 INDAHNYA KEBERSAMAAN SUBTEMA 1 KEBERAGAMAN BUDAYA BANGSAKU KELAS IV SEKOLAH DASAR - Lorensia Evi; Lusila Parida; Warkintin Warkintin (STKIP Persada Khatulistiwa Sintang, 2022)
This study aims to find out how the formation of students' moral values by utilizing local wisdom in Theme 7, the beauty of togetherness, sub-theme 1, the cultural diversity of my people in class IV. The approach used in this research is descriptive qualitative. Data collection techniques used in this study were observation techniques, interview techniques, and documentation techniques. Data collection tools in the form of observation sheets, interview guidelines, and documentation. The research informants were fourth grade teachers and 10 fourth grade students. The results showed that: 1) The implementation of the formation of students' moral values by utilizing local wisdom in Theme 7 The Beauty of Togetherness Sub-theme 1 Cultural Diversity of my Nation Class IV SDN 01 Tempunak can be carried out through four activities, namely: routine activities, spontaneous activities, exemplary and conditioning. 2) The factors that influence the formation of students' moral values by utilizing local wisdom in Theme 7 The Beauty of Togetherness Sub-theme 1 Cultural Diversity of my Nation class IV SDN 01 Tempunak basically consists of internal factors and external factors, namely internal factors in the form of: Lack of Effectiveness of Learning Curriculum, Lack of use of learning resources that contain local wisdom. External factors in the form of weak parental attention in supervising children's interactions outside school, lack of school cooperation with local community leaders. 3) the teacher's obstacles in influencing the formation of students' moral values by utilizing local wisdom in Theme 7 The Beauty of Togetherness Subtheme 1 Cultural Diversity of my Nation class IV SDN 01 Tempunak which consists of several obstacles, namely the misuse of mass media and the development of information technology which is used for negative things, the environment people who do not support local cultural expressions.